The pickling ability and adhesion edge scale of hot-rolled carbon steel produced using different entry temperatures - Ngamkham, Komsan; Trebooniti, Kantayut; Jenwilaisilp, Kasem; Phonsen, Decha; Wongyuen, Suwit (RMUTSB ACADEMIC JOURNAL, 2019)
The objective of this work was to investigate the pickling ability and the strain provoking the edge scale on hot-rolled carbon steel. The pickling test was conducted by immersing the steel samples in 10% v/v HCl solution both with and without industrial inhibitor at 80 oC. It was found that the addition of the inhibitor retarded the dissolution rate of the oxide scale, and this effect is more pronounced when the entry temperature was reduced from 1011 oC to 990 oC. However, in the solution without the inhibitor, the dissolution rates of the oxides formed using different entry temperatures were identical. From the previous work on scale adhesion assessment, the tensile test was applied to evaluate the scale of adherence. As a result, the derivative of the spallation ratio as a function of the imposed strain was calculated in order to determine the strain provoking the maximum spallation. The values were 3.78 ± 0.13% and 4.2 ± 0.28% for the hot-rolled steel produced using the entry temperatures of 1011 oC and 990 oC, respectively. The results showed that the entry temperature did not affect the edge scale adherence and pickling ability.